Foreign Inclusions, Enclosed Cavities, Partial Discharge Models and Discharge Energy: A Short Review Regarding Solid Dielectrics and Composite Insulating Systems - Danikas, M.; Morsalin, S. (Engineering, Technology & Applied Science Research, 2019)
Partial discharges in cavities are one of the main reasons of breakdown of insulating materials and insulating systems in general. The present paper aims at commenting some aspects of the relation between partial discharges and insulation damage. Some basic models explaining the workings and impacts of discharges in cavities are discussed. Discussions about the possibility of damage in the presence of multiple cavities as well as of the risks of minute discharges and/or charging phenomena below the so-called inception voltage are conducted. It is remarked that the question of the relationship between discharge parameters and insulation damage is still an important one, especially for composite insulating systems.